2010
DOI: 10.1111/j.1439-0442.1978.tb00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Half-life, Volume of Distribution and Acetylation of Sulphamerazine in Sheep

Abstract: Summary The half‐lives of sulphamerazine after intravenous, intramuscular and oral administration were estimated in sheep. The half‐lives indicated the presence of two phases, α and ß. The absorption phase (α) following oral and intramuscular routes was calculated as 180 ± 9 and 52 ± 4 minutes, respectively, whereas the distribution phase (α) after intravenous injection was 48 ± 4 minutes. The elimination half‐life (ß phase) in plasma was 340 ± 8 to 452 ± 10 minutes. The apparent volumes of distribution were 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1
0

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
4
1
0
Order By: Relevance
“…The dependance of the half-lives of drugs on the rate of metabolism (NIELSEN and RASMUSSEN, 1976) was also supported in the present study by the presence of a relatively larger amount of acetyl-sulphathiazole (1 6.2 O/o) than of the other 2 sulphonamides (7.1-8.4 Ole). Our results and those of other investigators (DAVITIYANANDA and RASMUSSEN, 1974; RAUWS et al, 1975;ATEF, 1978) indicate that ruminants have shorter elimination half-lives than other species. The relatively higher apparent volume of distibution of sulphathiazole (0.48) indicates higher distribution of the first in the tissues than of the other 2 drugs.…”
Section: Discussionsupporting
confidence: 85%
“…The dependance of the half-lives of drugs on the rate of metabolism (NIELSEN and RASMUSSEN, 1976) was also supported in the present study by the presence of a relatively larger amount of acetyl-sulphathiazole (1 6.2 O/o) than of the other 2 sulphonamides (7.1-8.4 Ole). Our results and those of other investigators (DAVITIYANANDA and RASMUSSEN, 1974; RAUWS et al, 1975;ATEF, 1978) indicate that ruminants have shorter elimination half-lives than other species. The relatively higher apparent volume of distibution of sulphathiazole (0.48) indicates higher distribution of the first in the tissues than of the other 2 drugs.…”
Section: Discussionsupporting
confidence: 85%
“…The elimination half-lives were less than those from cows in the case of sulphadiazine (324 min, ATEF et al, 1979 , and 330 min, LUTHER et al, 1977) and sulphadimidine (678 min, NIELSEN and RASMUSSEN, 1977) but higher than those for sulphathiazole (120 min, ATEF et al, 1979;90 min, NIELSEN andRASMUSSEN, 1977, and78 min, KORITZ et al, 1977). Our results and those of other investigators (DAVITIYANANDA and RASMUSSEN, 1974;RAUWS et al, 1975;ATEF, 1978, andLIMPOKA et al, 1977) indicated rhat ruminants have shorter elimination half-lives than other species. The results obtained here were consistent with those obtained by NIELSEN and RASMUSSEN (1977) and ATEF (1978) concerning the positive correlation between the 3 sulphonamides and their lipid solubilities and unionized fractions at p H 7.4 i. e. the more fatsoluble sulphadimidine is reabsorbed to a greater degree in the kidneys.…”
Section: Discussionsupporting
confidence: 83%
“…The comparatively faster elimination of sulphadiazine and sulphadimidine in buffaloes than in cows (LUTHER et al, 1977;RASMUSSEN, 1977, andATEF et al, 1979), could be attributed to their lower protein binding and/or higher rate of metabolism. The dependence of half-lives of drugs on their metabolic rate (NIELSEN and RASMUSSEN, 1976) is probably confirmed in this work by the presence of a relatively higher concentration of Nkicetylated derivatives in the urine of buffaloes (32.93-38.49 LUTHER et al, 1977), goats (7 O/O, ATEF and NIELSEN, 1975) ATEF, 1978) for differenit sulphonamides. O n the other hand, the faster elimination of sulphonamides injected into buffaloes than in man (STRULLER, 1968;BOHNI et al, 1969) was mainly related to the higher p H of buffalo urine (7.5-8.2) than human urine (5.0-7.5).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…For the 3 products the calculated half-life is greater after oral than after intravenous administration. This was also seen by several other workers (LINKENHEIMER and STOLZENBERG, 1965;KORIZ et al, 1977;ATEF, 1978, LOSCHet al, 1980. Plasma binding was approximately 89 O/o for sulfarnethylphenazole and much lower for the other substances.…”
Section: Resultssupporting
confidence: 79%